Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 18880 species occurrences available in GBIF matching the query: { "or" : [ "TaxonKey is Potentilla palustris (L.) Lehm.", "TaxonKey is Potentilla palustris (L.) Scop." ] } The dataset includes 18880 records from 178 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0016169-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences